Association between Height of the Patients and Cephalopelvic Disproportion in Primigravidas - Roshan, Samiya; Phulpoto, Maryam; Nigar, Roohi; Ahmad, Shakeel (Journal of Liaquat University of Medical & Health Sciences, 2021)
Objective: To determine the association between short stature and cephalo-pelvic disproportion among primigravida women with Pakistani population. Methodology: A case-control study was carried out after approval of CPSP from November 2018 to May 2019 at Obstetrics and Gynecology department of Jinnah Postgraduate Medical Center, Karachi. The primigravida pregnant women with the gestation age of 37 weeks or above and presented for a normal vaginal delivery with vertex presentation of the fetus and developed cepahalopelvic disproportion during labor was included in this study and primigravida pregnant women having an estimated fetal weight more than 3.5 Kg, patients having physical disability was excluded. A total of 238 primigravida patients fulfilling inclusion and exclusion criteria were selected. Informed consent was taken from each individual participated in this study. The age, height, gestational age, fetal mal-presentation, prolonged Labor, and caesarian delivery parameters were observed within the patients and data were analyzed through SPSS version 19. Results: The 21(17.6%) of patients with cephalopelvic disproportion was short suture in case group and 7(5.9%) in the control group, the results showed the significant association of cephalopelic disproportion with short suture patients. The ratio of caesarian delivery was also higher and a significant p-value was obtained. Conclusion: The mothers with cephalopelvic disproportion were independently correlated with a higher rate of short stature and caesarian rate is the highest among the CPS women. Key Words: Short stature, Cephalopelvic disproportion, Primigravida.